Unconventional materials in the contemporary sculptural composition: علاء محسن كَبيّش (Al-Academy, 2016)
This study aimed to knowledge of the effects of the Traditional ore upon the structure of sculpture form, as well as to knowledge of new materials that was used for the contemporary sculpture. This study included four chapter: first chapter was specialized for methodical frame. such as problem of research. that it was abstracted by question about the reason that lead the sculptor to search from new raw to carry out his sculpture works? As well as the important of research and its limits was that define between year 1950 up to 2000. The second chapter included the theoretical field and previous studies, that formed from three researches, such as the fist about the materials, as it was considered master element at the sculpture formal. the it included study about the widespread classic materials in the sculpture, such as ( clay , bronze, stones, and wood) and showing its effect and its formal and expression ability . The second research included the effects of Traditional raw at the formal system in the historical studies that included stylistic change during the twentieth century , and the third research included the study of the structural relations systems at the sculpture formation. The third chapter included the procedures of the research that its contents the research society such as European and American contemporary sculpture, and sample of research(fundamental) that was formed from (20) samples. It was choose according to the aim of this research. As well as performance of research based upon the analysis form, and this chapter included the following method at sample study as the analytic descriptive method in order to reach to the results, and conclusion that fixed in forth chapter